Ecological status of coral communities in Investigator Shoal of the Spratly Islands, South China Sea - Ivy Nathalie Semon; Daud Awang; Stephenie Demie Kawi; Mushidi Hassan; Mohd Sabry Saidin; Aiman Azseri; Nur Angelie Agnezara Roger; Andreana Doos; Zarinah Waheed; Muhammad Ali Syed Hussein; Mazni Muhammad Addin; Khairul Hisham Hariz; et al. (Springer Nature, 2025)
The Spratly Islands in the South China Sea are renowned for their remarkable reefs and serve as critical habitats for diverse corals and marine life. These reefs also provide livelihood benefits through fisheries and tourism, although their accessibility is limited due to remote location and geopolitical disputes. Despite the combined impacts of rampant and unregulated artificial island construction, along with outbreaks of Crown-of-Thorns Starfish (COTS), many reefs in the region remain ecologically significant and warrant conservation efforts. Investigator Shoal, a remote atoll in the Spratlys holds great potential for scientific exploration of its coral communities. This study aimed to assess the ecological status of coral reefs in this atoll by examining the condition, diversity and abundance of corals. Surveys were conducted using the Coral Video Transect (CVT) method at two different depths (10 m and 20 m) across ten reef sites. The data were analyzed using the Coral Point Count with Excel extension (CPCe) software. Overall, the reef assemblages showed a mean live coral cover of 46.4%±3.4, categorized as ‘Fair’ condition, with all reef sites had relatively high coral diversity. A total of 168 species from 64 genera and 22 families of hard and soft corals were identified. The soft coral Xenia, and the hard corals Acropora and Porites had the highest mean coverage and were abundant in the study area. Additionally, four rare and 19 vulnerable coral species were recorded, highlighting the ecological importance of these reefs despite the apparent impacts of land reclamation and COTS outbreak. The data presented in this study serve as baseline information for future conservation plans in the remote reefs of the Spratly Islands.